The natural history of untreated muscle‐invasive bladder cancer. (7th August 2019) - Martini, Alberto; Sfakianos, John P.; Renström‐Koskela, Lotta; Mortezavi, Ashkan; Falagario, Ugo G.; Egevad, Lars; Hosseini, Abolfazal; Mehrazin, Reza; Galsky, Matthew D.; Steineck, Gunnar; Wiklund, N. Peter
Abstract : Objective: To describe the natural history of untreated muscle‐invasive bladder cancer (MIBC) and compare the oncological outcomes of treated and untreated patients. Patients and Methods: We utilised a database encompassing all patients with newly diagnosed bladder cancer in Stockholm, Sweden between 1995 and 1996. The median follow‐up for survivors was 14.4 years. Overall, 538 patients were diagnosed with bladder cancer of whom 126 had clinically localised MIBC. Patients were divided into two groups: those who received radical cystectomy or radiation therapy, and those who did not receive any form of treatment. Multivariable Cox or competing‐risks regressions were adopted to predict metastasis, overall survival (OS), and cancer‐specific mortality (CSM), when appropriate. Analyses were adjusted for age at diagnosis, sex, tumour stage, clinical N stage, and treatment. Results: In all, 64 (51%) patients did not receive any definitive local treatment. In the untreated group, the median (interquartile range) age at diagnosis was 79 (63–83) vs 69 (63–74) years in the treated group ( P  < 0.001). Overall, 109 patients died during follow‐up. At 6 months after diagnosis, 38% of the untreated patients had developed metastatic disease and 41% had CSM. The 5‐year OS rate for untreated and treated patients was 5% (95% confidence interval [CI] 1, 12%) vs 48% (95% CI 36, 60%), respectively. Patients not receiving any treatment had a 5‐year cumulative incidence of CSM of 86% (95% CI 75, 94%) vs 48% (95% CI 36, 60%) for treated patients. Untreated patients had a higher risk of progression to metastatic disease (hazard ratio [HR] 2.40, 95% CI 1.28, 4.51; P  = 0.006), death from any cause (HR 2.63, 95% CI 1.65, 4.19; P  < 0.001) and CSM (subdistribution HR 2.02, 95% CI 1.24, 3.30; P  = 0.004). Conclusions: Untreated patients with MIBC are at very high risk of near‐term CSM. These findings may help balance the risks vs benefits of integrating curative intent therapy particularly in older patients with MIBC.